Comparing Journalistic Role Performance Across Thematic Beats: A 37-Country Study (2023)
Studies suggest that, at the routine level, news beats function as unique “micro-cultures.” Exploring this “particularist” approach in news content, we compare how the interventionist, watchdog, loyal, service, infotainment, and civic roles materialize across 11 thematic news beats and analyze the moderating effect of platforms, ownership, and levels of political freedom on journalistic role performance in hard and soft news. Based on the second wave of the Journalistic Role Performance (JRP) project, this article reports the findings of a content analysis of 148,474 news items from 37 countries. Our results reveal the transversality of interventionism, the strong associations of some topics and roles, and the limited reach of news beat particularism in the face of moderating variables.